Monitoring and analyzing exoplanetary transits from Argentina - Fernández Lajús, Eduardo (2010)
Photometric observations of transits can be used to derive physical and orbital parameters of the system, like the planetary and stellar radius, orbital inclination and mean density of the star. Furthermore, monitoring possible periodic variations in transit timing of planets is important, since small changes can be caused by the presence of other planets or moons in the system. On the other hand, long term changes in the transit length can be due to the orbital precession of the planets. For these reasons we started an observational program dedicated to observe transits of known exoplanets with the aim of contributing to a better understanding of these planetary systems. In this work we present our first results obtained using the observational facilities in Argentina including the 2.15 telescope at CASLEO.